The development of morality from Paulo Freire's pedagogy of autonomy - Solís Vargas, Yors Guillermo (Innovaciones Educativas, 2022)
The essay aims to carry out a theoretical analysis of the need to formally develop morality from basic general education in Costa Rica. For this task, Freire's pedagogy of autonomy was taken as the essential foundation of what a proposal for autonomous, critical and responsible moral formation with society can represent. Within the text you can also find theoretical analyzes and references to non-Latin American authors who have researched on this subject, who affirm that morality can be taught and can be formally developed but, in the end, Freirean pedagogy stands out as the basis for this type. of development in the country. The main conclusion is that it is possible and viable to formalize, plan and execute formally and in conjunction with the other subjects of the curriculum a critical and autonomous morality from an early age.